Agricultural Productivity and Child Mortality: The Impact of the Green Revolution. Issue 1 (1st March 2014) - Rosegrant, Mark W.; Evenson, Robert E.; Msangi, Siwa; Sulser, Timothy B.
Abstract : "This paper is dedicated to the memory of Robert E. Evenson. Bob was a great teacher and advisor to hundreds of students at Yale and in the Philippines, many of whom have gone on to highly successful careers. Bob was a leading scholar in research related to agri—cultural research, economic development, and education." Many papers have examined the impact of the Green Revolution and the international agricultural research centers on agricultural productivity and the rates of return to agricultural research investment. Here we extend this analysis to look at the impact on food security and human welfare as measured by child mortality. In this paper, we conduct two counterfactual simulations for the 30‐year period 1970–2000—the first holding 1970 crop genetic improvements constant and the second presuming the International Agricultural Research Center (IARC) system had not been built. Our results show that Green Revolution technologies and the IARC system significantly reduced child mortality. The counterfactual analysis demonstrates the importance of the Green Revolution in generating not only sustained improvements in crop productivity growth through the 1970s and 1980s, but also the powerful indirect effects on human welfare as measured by child mortality.